Revamping existing glycol technologies in natural gas dehydration to improve the purity and absorption efficiency: Available methods and recent developments - Kong, Z.; Mahmoud, A.; Liu, Shaomin; Sunarso, J. (Elsevier Inc., 2018)
© 2018 Elsevier B.V. The glycol purity limit in conventional absorption-based natural gas dehydration process has led to the significant water vapour presence in the supposedly dry product gas. Several alternative processes have been developed to overcome this limitation that includes stripping gas injection using nitrogen, a portion of dry product gas, or volatile hydrocarbon (DRIZO process), stripping gas modified with Stahl column, and Coldfinger technology. This review summarises these different processes and elaborates on their mechanisms, process flow diagram, advantages, drawbacks, and current statuses. Relevant works from 1991 to 2017 were compiled and the existing gaps were highlighted as recommendation for future work.